Assistência de ar na deposição e perdas de produtos fitossanitários em pulverizações na cultura da soja - Bauer, Fernando César; Raetano, Carlos Gilberto [UNESP] (São Paulo - Escola Superior de Agricultura "Luiz de Queiroz", 2000)
The spray deposition and losses of pesticide application were evaluated for the soybean crop. In this study two sprayers were used: the air-assisted sprayer (Vortex-Jacto) and the conventional non-assisted sprayer (Condor M12-Jacto), both with API 110-1.5 flat fan nozzles operating at 30 psi working pressure, with 0.5 m spacing on the boom. Volume rates were 100 L ha-1 for both equipments. A completely randomized experiment with four replicates was carried out in the field. For all treatments, the ground speed was 6 km h-1 and boom height was 0.40 m above canopy. Spray deposition and losses were evaluated using 2% KCl and NaCl solutions in air-assisted and conventional non assisted sprayers. Deposition evaluations were performed on leaves from the upper, medium and lower parts of the soybean plant. Spray losses to the soil were evaluated using artificial targets (square wood board) that were distributed on the soil surface at intervals of 3 m from each other. Drift was evaluated through these targets and pipe cleaners fixed on rods placed at the left and right sides at the crop. There were no significant differences in the deposition for both equipments in the upper parts of the plants, but there were differences in the medium and lower parts, showing an advantage of the air-assisted sprayer. Drift and losses were larger for the conventional non assisted sprayer at similar meteorological conditions.

Com o objetivo de se comparar a deposição e as perdas em pulverizações na cultura da soja dois pulverizadores tratorizados de barra sendo um convencional (Condor M12-Jacto) e outro com assistência de ar junto a barra de pulverização (Columbia Vortex-Jacto) foram calibrados para aplicar 100 L ha-1, respectivamente das soluções de NaCl e KCl a 2% (p/v) à pressão de 207 kPa (30 lbf pol-2)e velocidade de 6 km h-1. Ambos os equipamentos utilizaram bicos de jato plano tipo API 110-1,5 espaçados a 0,5 m trabalhando a 0,4 m acima da cultura. A avaliação da deposição deu-se em folhas das partes superior, média e inferior das plantas e as perdas para o solo em alvos artificiais (placas de fórmica) distribuídos no interior da cultura de soja. Além desse alvo artificial outros tipos de coletores (limpadores de cachimbo) também foram utilizados em ambos os lados da cultura para se estimar a deriva. Os resultados mostraram que não houve diferença significativa na deposição entre os equipamentos em teste na parte superior das plantas de soja, mas houve diferença significativa nos depósitos obtidos nos terços médio e inferior, com vantagem para o equipamento com assistência de ar. A deriva foi consideravelmente maior para o equipamento convencional nas mesmas condições meteorológicas.
Air-assisted sprayer for the evaluation of deposition and losses of pesticide application to soybean crop
Keywords: Glycine max; mechanized sprayer; Glycine max; pulverizador tratorizado